DISTRIBUTION OF HUMANITARIAN AID TO THE MIFTAHUL JANNAH ORPHANAGE AFFECTED BY FLOODS - Rico Nur Ilham; Irada Sinta; Likdanawati; Hamdiah; Muttaqien; Reza Juanda (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2025)
Floods are one of the most frequent natural disasters in Indonesia and have a significant impact on vulnerable groups, including children living in orphanages. Miftahul Jannah Orphanage is one of the social institutions affected by the floods, disrupting their caregiving activities, health, and the psychosocial well-being of the children. This study aims to analyze the process and impact of the distribution of humanitarian aid to Miftahul Jannah Orphanage after the floods. The method used is a descriptive qualitative approach with a case study design. Data collection was conducted through field observations, semi-structured interviews with orphanage administrators, orphanage children, and volunteers, and documentation of aid distribution activities. Data were analyzed using thematic analysis to identify patterns of needs, benefits of aid, and implementation challenges. The results show that the distribution of humanitarian aid has a positive impact on meeting basic needs, improving environmental hygiene and health, and restoring the psychosocial conditions of orphanage children. However, challenges remain in the logistical aspects and sustainability of aid. This study concludes that needs-based humanitarian assistance, targeted at vulnerable groups, and integrating material assistance and psychosocial support, is crucial for supporting sustainable post-disaster recovery. These findings are expected to serve as a reference for the development of future humanitarian assistance and community service programs.